2012
DOI: 10.1371/journal.pone.0050199
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-7, but Not Thymic Stromal Lymphopoietin, Plays a Key Role in the T Cell Response to Influenza A Virus

Abstract: The immune response to viral infection is ideally rapid and specific, resulting in viral clearance and establishment of immune memory. Some viruses such as HIV can evade such responses leading to chronic infection, while others like Influenza A can elicit a severe inflammatory response with immune-related complications including death. Cytokines play a major role in shaping the appropriate outcomes to infection. While Interleukin-7 (IL-7) has a critical role in T and B cell development, treatment with IL-7 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Our model suggests that CD4 + T cell expansion in cells undergoing LIP is regulated by an IL-7-dependent signaling composed by activation of STAT1 and STAT5, and this mechanism limits the expansion of the CD4 + T cell pool. The transcription of STAT1/IFN-associated genes may also reflect other potential properties of IL-7 (47,48). Recently, we have described that IL-7 can potentiate the responsiveness of T cells to type I IFNs by modulating the expression levels of STAT1 (37).…”
mentioning
confidence: 99%
“…Our model suggests that CD4 + T cell expansion in cells undergoing LIP is regulated by an IL-7-dependent signaling composed by activation of STAT1 and STAT5, and this mechanism limits the expansion of the CD4 + T cell pool. The transcription of STAT1/IFN-associated genes may also reflect other potential properties of IL-7 (47,48). Recently, we have described that IL-7 can potentiate the responsiveness of T cells to type I IFNs by modulating the expression levels of STAT1 (37).…”
mentioning
confidence: 99%
“…I nterleukin-7 is a critical cytokine for the development of B and T cells, the development of antiviral T cell responses and maintenance of memory T cells (1)(2)(3)(4). Thymic stromal lymphopoietin (TSLP) is a related cytokine important in Th2 responses and immunity at mucosal sites (5).…”
mentioning
confidence: 99%
“…While it has been reported that TSLP-R −/− cells express lower levels of the inflammatory chemokine receptor CXCR3 (37), TSLP-R −/− OT-I cells were able to accumulate in the respiratory tract (Fig. 4), indicating to us that loss of TSLP did not impact migration to the mucosa.…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, TSLP expression was also enhanced following infections with the respiratory pathogens Rhinovirus and Respiratory syncytial virus in human and rat airway epithelial cells, respectively (35). Recently, it has also been shown that infection with the highly pathogenic strain of influenza A virus, Puerto Rico/8 (PR8) can induce the production of TSLP mRNA in the lungs and trachea of mice (36), although data is conflicting as to whether or not this affects the anti-influenza CD8 T cell response, either directly or indirectly, and to what extent (36, 37). …”
Section: Resultsmentioning
confidence: 99%